A Review on (Hydro)Porphyrin-Loaded Polymer Micelles: Interesting and Valuable Platforms for Enhanced Cancer Nanotheranostics - Nascimento, Bruno F. O. (2019)
Porphyrins are known therapeutic agents for photodynamic therapy of cancer and also imaging agents for NIR fluorescence imaging, MRI, or PET. A combination of interesting features makes tetrapyrrolic macrocycles suitable for use as theranostic agents whose full potential can be achieved using nanocarriers. This review provides an overview on nanotheranostic agents based on polymeric micelles and porphyrins developed so far.